Ego defense mechanisms, medication adherence and self-management of the patients with type 2 diabetes - Fatima Akram; Mahwesh Arooj Naz (Journal of the Pakistan Medical Association, 2020)
Objective: To explore relationship involving Ego Defence Mechanism, Medication Adherence and Self-Management of patients with type 2 diabetes. Method: The cross-sectional co-relational study was conducted at the Government College University, Lahore, Pakistan, from November 2017 to November 2018, and comprised diabetics aged 25-55 years. Other than demographic information, data was collected using the Urdu versions of the Defense Style Questionnaire, the Medication Adherence Scale, and the Diabetic Self-management Questionnaire. Data was analysed using SPSS 22. Results: Of the 150 patients, 75(50%) each were females and males. Mature defence mechanisms, like sublimation, suppression and humour, were significant predictors of self-management (p<0.001), and mature defence mechanism, like sublimation, was a significant predictor of medication adherence (p<0.05). Females were high on neurotic defence mechanism, like pseudo-altruism, compared to the males (p=0.001). Conclusion: Medication adherence and self-management were found to be dependent on mature defence mechanisms. Key Words: Ego defence mechanisms, Medication adherence, Self-management, Immature defences, Mature defences, Neurotic defences. Continuous...